Testing Language Vitality Instuments: Falsification and Language Status Evaluation - Budiono, Satwiko (Journal of Languages and Language Teaching, 2025)
Different instruments for language vitality are used to determine language status. However, doing so raises problems regarding the correctness of an instrument, especially in terms of differences in instruments among qualitative, quantitative, and mixed methods. This aspect exerts an impact on differences in the svariables of respondent criteria, data collection techniques, and the categorization of results. Moreover, a few of these instruments cannot necessarily be applied to all languages in Indonesia due to complex conditions. Moreover, this research is novel because it is the first to discuss linguistic theory using a philosophical approach, especially falsification approach. This aims to test validity of language vitality instruments. Furthermore, it attempts to identify instruments that can be applied to languages in Indonesia. The reason is that Indonesia features many local languages, which leads to complex linguistic situations and conditions. This research uses a descriptive qualitative methods. Research techniques use data taken from previous studies and observations. Data analysis uses Popper’s falsification theory. The result indicated that language vitality instruments require several new alternative theories to address the complex linguistic conditions in Indonesia. The principle of falsification can add truth value in determining language status, such that it can be accepted for all languages in Indonesia. However, the falsification is still required for minority languages and strengthens the truth value of languages that are extinct. This notion exerts a contribution on the deepening of language policy in Indonesia, such that all languages can undergo language vitality testing according to the characteristics of their languages.